The effect of organizational and manager’s individual characteristics on the use of balanced scorecard and performance (evidence from local government of Indonesia) - Yulia Tri Kusumawati; Praja Hadi Saputra (INOVASI, 2022)
The purpose of this study was to investigate the factors that motivated managers to use the Balanced Scorecard in public sector organizations in local government in Indonesia and how the impact of BSC usage on the performance improvement. We use survey method to collect the data with a total of 45 respondents. This study uses a SEM-PLS analysis to test the research hypothesis. Survey technique was through a questionnaire to determine the motivation of the head of department in utilizing BSC. The results indicate that organizational factors (availability of IT resources) and individual characteristics of managers (flexible manager evaluation styles) were positively and significantly related to motivation to use BSC which then had a positive impact on improving organizational performance. Meanwhile the rigid evaluation style of the manager (rigid evaluation) was negatively and significantly related to the motivation to use BSC, which then had an impact on the decline of the organization performance.